KENDALA YANG DIHADAPI OLEH KEMENTERIAN LUAR NEGERI INDONESIA BAGI PENYELESAIAN KASUS TENAGA KERJA INDONESIA OVERSTAYERS DI ARAB SAUDI (2014-2015) - Anggita Setyowati (HI 16 UMY 066, 2016)
*66 This thesis discusses the constraints faced by the foreign ministry in resolving the case of Indonesian workers in saudi Arabia overstayers. TKI overstayed itself are those who live beyond the final deadline visa or residence permit in the country where they work, without an extension of the document. The framework of this thesis uses the theory of public policy implementation and political systems theory. The results showed that the Ministry of Foreign Affairs faced constraints from the internal environment and the external environment. Of internal itself comes from within the country, and externally originated from the Saudi Arabia. Keywords: Ministry of Foreign Affairs, TKI Overstayer, Constraints of Intrasocietal, Constraints of Extrasocietal.